2020
DOI: 10.1002/brb3.1911
|View full text |Cite
|
Sign up to set email alerts
|

AG490 protects cerebral ischemia/reperfusion injury via inhibiting the JAK2/3 signaling pathway

Abstract: Background Cerebral ischemia/reperfusion injury is a severe problem in patients with brain ischemia. Brain injury caused by the immune response is important in the pathogenesis of cerebral ischemia/reperfusion injury and immune pathways. It is important to investigate potential targets for the treatment of cerebral ischemia/reperfusion injury. Methods In this experiment, we evaluated the effect of an exogenous JAK antagonist AG490 in the cerebral ischemia/reperfusion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…The above results indicated that AG490 partially blocked or reduced intracellular signal transduction of inflammatory cytokines by inhibiting JAK2 phosphorylation and STAT3 tyrosine phosphorylation. Our results agreed with the results of international researchers (Yang et al, 2017;Fan & Zhou, 2021b;Liang et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The above results indicated that AG490 partially blocked or reduced intracellular signal transduction of inflammatory cytokines by inhibiting JAK2 phosphorylation and STAT3 tyrosine phosphorylation. Our results agreed with the results of international researchers (Yang et al, 2017;Fan & Zhou, 2021b;Liang et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Satriotomo et al (2006) reported a close connection between STAT3 phosphorylation and neuronal death in cerebral ischemia. Downregulation of JAK2/STAT3 activation improves nerve function and achieves neuroprotective effects in focal cerebral ischemia (Fan & Zhou, 2021b). Neuroprotective effect against CIRI can be activated by the JAK/STAT3 inhibitors like AG490 (Yang et al, 2017;Liang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral ischemia causes activation of the Jak2 signaling pathway, which is closely related to the occurrence of poststroke brain injury. Inhibiting activation of the Jak2 signaling pathway can inhibit neuronal apoptosis, thereby alleviating brain injury [ 28 , 29 , 30 , 31 , 32 ]. Conversely, the activation of the Jak2 signaling pathway is also pivotal in the cerebral ischemia neuroprotective actions of melatonin, resveratrol, leptin, and erythropoietin derivatives [ 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, either with the reduction of IL-6 levels through anti-inflammatory treatments or the intravenous injection of IL-6 neutralizing antibodies, cerebral ischemic damage can be alleviated [ 24 , 25 , 26 , 27 ]. Besides this, the inhibition of the Jak2/Stat3 pathway that can be activated with excess IL-6 during the acute phase of cerebral ischemia confers neuroprotection in ischemic stroke [ 28 , 29 , 30 , 31 , 32 , 33 ]. Taken altogether, these findings indicated the deleterious effects of IL-6 on neuronal injury after cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a study on autism found that resveratrol could compete with neuroimmune dysfunction by downregulating proinflammatory cytokines, such as IL‐6, and the JAK1/STAT3 pathway in BTBR mice (Ahmad, Ansari, et al., 2018). Moreover, inhibition of the JAK2/STAT3 pathway is essential in neuroprotection after CIRI (Fan & Zhou, 2021). The JAK2/STAT3 pathway plays a critical role in the inflammatory reaction, which is necessary for the function of cytokines, the differentiation of T lymphocytes, and the activation of adaptive immunity (O'Shea et al., 2015).…”
Section: Introductionmentioning
confidence: 99%